Managerial forensics - Munoz, J. Mark. (Corporate governance collection., 2016)
Managerial forensics is the practice of gathering relevant corporate information for the purpose of analyzing and identifying reasons for managerial obstacles, mismanagement, bankruptcy, and corporate demise. This book assembles a cast of leading academic and business experts and shares their views on the best practices in corporate analysis. Following the notion that the past offers insights into the future, the book examines the maladies in contemporary business and offers strategies for corporate revival and turnaround.